Kebijakan Kredit Melalui Bank Perkreditan Rakyat Bagi UMKM Dalm Meningkatkan Pertumbuhan Ekonomi Nasional - ulfanora nanda nanda; nanda utama utama (Fakultas Hukum Universitas Riau, 2023)
Credit policy is a state goal to provide opportunities for the community to build businesses or businesses that have an impact on the nation's economic drive systemically. Banking financial institutions that serve credit financing products as products that are often in demand by customers in order to open a business by offering a prospectus for business activities. The existence of Rural Banks (BPR) has a significant role for local communities in the context of regional economic development. Broadly speaking, the role of BPR is not only in channeling funds to the public, but the bank and its customers work together to build a project through a financing product called profit sharing (dividend). The research method uses normative juridical (doctrinal research) with a qualitative approach, which in processing and analyzing data does not use numbers, symbols, and mathematical variables, but rather an in-depth understanding by reviewing the laws and regulations. The results of the study explain that, Developments in credit policy resulted in a change and were able to overcome the problem of instability in a country. Rural Banks have a policy of limiting credit distribution which is regulated in a regulation in order to achieve a productivity of capital to be distributed. The government through the Job Creation Law is to create an MSME ecosystem that is more integrated with investment and workers (human resources) for the sake of sustainability and the continuity of productive capital distribution. With the people's credit policy, regional creative products can be recognized and provide business opportunities for business actors in the region